The impact of glycosylation on the biological function and structure of human immunoglobulins. - Arnold, J; Wormald, M; Sim, R; Rudd, P; Dwek, R (2007)
Immunoglobulins are the major secretory products of the adaptive immune system. Each is characterized by a distinctive set of glycoforms that reflects the wide variation in the number, type, and location of their oligosaccharides. In a given physiological state, glycoform populations are reproducible; therefore, disease-associated alterations provide diagnostic biomarkers (e.g., for rheumatoid arthritis) and contribute to disease pathogenesis. The oligosaccharides provide important recognition epitopes that engage with lectins, endowing the immunoglobulins with an expanded functional repertoire. The sugars play specific structural roles, maintaining and modulating effector functions that are physiologically relevant and can be manipulated to optimize the properties of therapeutic antibodies. New molecular models of all the immunoglobulins are included to provide a basis for informed and critical discussion. The models were constructed by combining glycan sequencing data with oligosaccharide linkage and dynamics information from the Glycobiology Institute experimental database and protein structural data from "The Protein Data Bank."